2002
DOI: 10.1139/w02-049
|View full text |Cite
|
Sign up to set email alerts
|

Hollow-fiber ultrafiltration ofCryptosporidium parvumoocysts from a wide variety of 10-L surface water samples

Abstract: An optimized hollow-fiber ultrafiltration system (50 000 MWCO) was developed to concentrate Cryptosporidium oocysts from 10-L samples of environmental water. Seeded experiments were conducted using a number of surface-water samples from the southwestern U.S.A. and source water from four water districts with histories of poor oocyst recovery. Ultrafiltration produced a mean recovery of 47.9% from 19 water samples (55.3% from 39 individual tests). We also compared oocyst recoveries using the hollow-fiber ultrafi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
35
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 17 publications
7
35
1
Order By: Relevance
“…Consistent with previous work (8,9,26), the washing procedures were effective in completely removing protozoa and viruses. When bacterial growth was observed, additional cycles of sanitization were done until the plate counts were zero.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Consistent with previous work (8,9,26), the washing procedures were effective in completely removing protozoa and viruses. When bacterial growth was observed, additional cycles of sanitization were done until the plate counts were zero.…”
Section: Resultssupporting
confidence: 87%
“…Previous work has shown that Tween 80 stabilizes virus and improves elution (9,11), and the nonionic detergent probably prevented the adhesion of cells to the ultrafilter membrane surface in our study. However, though serovar Enteritidis recoveries doubled in the presence of Tween 80, recoveries remained highly variable, especially in contrast to the consistent recoveries of the two E. coli strains used.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The 1622 method detects and calculates only Cryptosporidium oocysts in water samples; the 1623 method -Cryptosporidium oocysts and Giardia cysts, and introduces some improvements. However, the recovery of oocysts from environmental water samples with the use of these both methods has been reported to be very variable (Simmons et al 2001;Kuhn and Oshima 2002;Wohlsen et al 2004;Krometis et al 2009;Karim et al 2010). With regard to this fact, matrix spikes are routinely analysed to determine the influence of environmental matrices on the effectiveness of the methods for detecting target organisms (Francy et al 2004).…”
mentioning
confidence: 99%